2019
DOI: 10.4097/kja.d.18.00208
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of heart rate between natural sleep and dexmedetomidine sedation

Abstract: Background Sedation by dexmedetomidine, like natural sleep, often causes bradycardia. We explored the nature of heart rate (HR) changes as they occur during natural sleep versus those occurring during dexmedetomidine sedation. Methods The present study included 30 patients who were scheduled to undergo elective surgery with spinal anesthesia. To assess HR and sedation, a pulse oximeter and bispectral index (BIS) monitor were attached to the patient in the ward and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…There was no significant difference in the post-operative heart rate between the Single and Continuous groups, because the continuous dexmedetomidine infusion reduced the heart rate in both groups. Earlier studies demonstrated the heart rates were lower in patients who received a dexmedetomidine infusion [7][8][9] . In contrast, the pain management due to the continuous field block in the present study reduced the respiratory rate in the Continuous group.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the post-operative heart rate between the Single and Continuous groups, because the continuous dexmedetomidine infusion reduced the heart rate in both groups. Earlier studies demonstrated the heart rates were lower in patients who received a dexmedetomidine infusion [7][8][9] . In contrast, the pain management due to the continuous field block in the present study reduced the respiratory rate in the Continuous group.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, a selective α 2 adrenergic receptor agonist, has sedative and analgesic properties. Its sedation is similar to that of natural sleep; therefore, it is known to cause less respiratory depression [ 15 ]. However, the advantage of being similar to natural sleep implies that the incidence rate of OSA is high, as reported by Shin et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DEX-induced bradycardia has, to date, not been reported to be of clinical relevance or require pharmacologic treatment. In adults, the drop in heart rate during DEX sedation mimics the heart rate response observed during natural and DEX-induced sleep in adults: Natural and DEX-induced sleep demonstrated changes in heart rate that were not statistically different [ 49 ]. Further studies will be important to determine whether, similar to adults, the heart rate response to DEX in the pediatric population is similar to those observed during natural sleep.…”
Section: Updates On End-organ Effectsmentioning
confidence: 99%